2008
DOI: 10.1111/j.1551-2916.2008.02625.x
|View full text |Cite
|
Sign up to set email alerts
|

New Cementitious Materials Based on Alkali‐Activated Fly Ash: Performance at High Temperatures

Abstract: This paper reports on a comparative study of the mechanical performance at different temperatures of a commercial Portland cement, used as a control, and a new cementitious material made from an 8M-NaOH activated fly ash and containing no OPC. Two types of mechanical tests were conducted: (i) high temperature mechanical tests, to determine the strength and fracture toughness of the two materials between 251 and 6001C, and (ii) post-thermal treatment tests, to evaluate the residual strength after 1 h of exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(80 citation statements)
references
References 27 publications
4
70
0
6
Order By: Relevance
“…F5S0, which is a purely fly ash-based foam and thus contains a solely aluminosilicate gel, maintains its strength at 400°C, and increases by 11 50% after heating to 800°C. The good compressive strength retention up to 400°C (actually slight increase in this study) was also observed in the dense 8 M NaOH-activated fly ash binder [29]; the remarkable strength increase of F5S0 at 800°C is in agreement with these reported results. Rickard et al [30] also showed that the strengths of solid geopolymers increase after exposure to 1000°C, when low iron and low calcium-bearing fly ashes are used.…”
Section: Thermal Resistancesupporting
confidence: 82%
“…F5S0, which is a purely fly ash-based foam and thus contains a solely aluminosilicate gel, maintains its strength at 400°C, and increases by 11 50% after heating to 800°C. The good compressive strength retention up to 400°C (actually slight increase in this study) was also observed in the dense 8 M NaOH-activated fly ash binder [29]; the remarkable strength increase of F5S0 at 800°C is in agreement with these reported results. Rickard et al [30] also showed that the strengths of solid geopolymers increase after exposure to 1000°C, when low iron and low calcium-bearing fly ashes are used.…”
Section: Thermal Resistancesupporting
confidence: 82%
“…The fact that certain zeolites were, however, would appear to indicate that part of the amorphous gel may have converted into secondary crystalline reaction products such as Na-chabazite, also known as herschelite (R) (NaAlSi 2 O 6 .3H 2 O), and sodalite, otherwise denominated hydroxysodalite (S) (Na 4 Al 3 Si 3 O 12 OH) -. The presence of these compounds, also reported by other authors studying alkali-activated fly ash systems (45)(46)(47)(48), was confirmed by scanning electron microscopy, as shown in Figure 5. While both types of zeolites were found in the two systems, they were more abundant in FA-M3.…”
Section: Caracterización Mineralógica Y Microestructural De Los Sistesupporting
confidence: 64%
“…Lógicamente, esta fase no se identificó por DRX, pero sí se detectó la presencia de zeolitas, lo cual parece indicar que parte del gel amorfo se pudo transformar en un producto de reacción secundario cristalino correspondiente a Na-Chabacita o también llamada Herschelita (R) (NaAlSi 2 O 6 .3H 2 O) y sodalita o también llamada Hidroxisodalita (S) (Na 4 Al 3 Si 3 O 12 OH); estos compuestos han sido igualmente reportados por otros autores en sistemas de cenizas volantes activadas alcalinamente (45)(46)(47)(48). La presencia de estas zeolitas se confirma mediante microscopia electrónica de barrido tal como puede observarse en la Figura 5.…”
Section: Caracterización Mineralógica Y Microestructural De Los Sisteunclassified
“…There is a synergy between the parameters studied that can be better understand by the mineralogical and microstructural characterization of raw materials and final products [23], which are determined by X-ray diffraction or thermogravimetric analysis [24][25][26]. Most of studies on the geopolymer development report only compressive strength and x-ray diffraction results.…”
Section: Justificationmentioning
confidence: 99%